Clinical Outcomes After Endovascular Repair and Open Surgery to Treat Immunoglobulin G4–Related and Nonrelated Inflammatory Abdominal Aortic Aneurysms. (December 2017) - Kasashima, Satomi; Kasashima, Fuminori; Kawashima, Atsuhiro; Endo, Masamitsu; Matsumoto, Yasushi; Kawakami, Kengo
Purpose: To compare the follow-up results of endovascular aneurysm repair (EVAR) vs open surgery (OS) for inflammatory abdominal aortic aneurysms (IAAAs) with regard to immunoglobulin G4–related diseases (IgG4-RD), which are fibrous inflammatory conditions characterized by elevated serum IgG4 concentrations and numerous infiltrations of IgG4 + plasmacytes.Methods: Between January 2005 and December 2015, 91 patients were treated with EVAR (begun in 2008) and 166 patients underwent OS for AAA. Forty of these 257 patients had IAAAs identified by a >2-mm thickness of periaortic fibrosis (PAF). Of these 40, 21 had pathologically confirmed IgG4-RD and/or serum IgG4 concentrations ≥135 mg/dL (classified IgG4+); 8 (mean age 76 years; 8 men) were treated with EVAR and 13 (mean age 71 years; 11 men) underwent OS. Of the 19 IgG4– patients with IAAA, 9 (mean age 71 years; 8 men) had EVAR and 10 (mean age 75 years; 9 men) had OS. The 4 subgroups were compared in terms of symptoms, complications, inflammation markers, PAF, and aneurysm diameter using the latest midterm follow-up data (12–24 months).Results: Preoperative aneurysm diameter, PAF, gender, median age, symptoms, and median follow-up period were similar in all groups. Preoperative serum IgG4 was equal in EVAR and OS IgG4+ groups. Compared with the OS IgG4+ group, EVAR IgG4+ patients more frequently had postoperative IgG4 increase (5/8; p=0.006) and PAF progression (5/8; p=0.027), higher postoperative serum IgG4 levels (median 141 mg/dL; p=0.034), a thicker postoperative PAF (median 5.1 mm; p=0.016), and persistent clinical symptoms (p=0.006). Compared with EVAR IgG4– patients, the EVAR IgG4+ patients showed significantly thicker postoperative PAF (p=0.024) and larger increases in postoperative sac diameter (median +13.1 mm; p=0.030). Postoperative PAF and sac diameter frequently and synchronously became worse in the EVAR IgG4+ subgroup with increased IgG4 during follow-up. The rate of change in IgG4 significantly positively correlated with the rates of change in PAF (R=0.555, p=0.03) and sac diameter (R=0.902, p=0.003).Conclusion: Though sample sizes were rather small, this pilot study suggested that EVAR-treated IgG4+ IAAA patients have a higher risk of persistent symptoms and increases in PAF, sac diameter, and IgG4 levels. Therefore, OS should be preferred for complete recovery. Frequent monitoring of the postoperative serum IgG4 is necessary following EVAR in IgG4+ patients to detect these complications.